Six-week grit training course reduces school bullying: A quasi-experimental study - Wang, Lei; Chen, Qianqian; Peng, Zhenzhen; Ye, Caixia; Zhou, Xinyi (Frontiers in Child and Adolescent Psychiatry, 2023)
Objective To investigate the effectiveness of intervention programs in reducing school bullying, a 6-week series of grit training courses was designed and developed. Methods Using a quasi-experimental design, 163 middle school students were selected as the experimental group and 201 middle school students as the control group to test the implementation effect of the grit training course. Results The intervention program significantly reduced the traditional bullying behavior of the bullies and the traditional victimization of victims. Conclusion The 6-week grit course has produced positive results in reducing school bullying. In the future, school-based courses with the theme of grit can be designed to achieve the purpose of preventing school bullying by improving the positive qualities of individuals.